Derivative products and innovation in Islamic finance. Issue 3 (12th August 2014) - Kiong Kok, Seng; Giorgioni, Gianluigi; Laws, Jason
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to highlight the possibility of structuring an Islamic option which includes an element of risk sharing as opposed to risk transfer. Design/methodology/approach – The approach adopted in this research involved a combination of a wa'ad (promise) and murabaha (cost plus sale) and examining if they could form a risk-sharing Islamic option. The payoffs were assumed to be dependent on bi-period outcomes. Findings – The paper attempted to create a hybrid risk-sharing option by combining elements of both wa'ad (promise) and murabaha (cost plus sale). The results yielded are dependent on the eventual direction of the market (in-the-money, at-the-money and out-the-money). While the results are not definitive, they do provide arguments for the adoption of a risk-sharing, as opposed to a risk-transfer, methodology when it comes to structuring risk management instruments. Research limitations/implications – One of the major limitations of this research is the inability to assess the Shariah compliance of the proposed instrument. Shariah compliance is determined by a Shariah Supervisory Board, and every effort has been made to ensure that Shariah financial principles are adhered to in the creation of this structure. Practical implications – The structure provides some interest arguments in the creation of risk management tools under a Shariah financial framework. The structure illustrates the benefits of having a risk-sharing mode over the conventional risk-transfer stances of most risk management tools. Originality/value – The paper offers a new way of structuring a risk management tool in Islamic finance. It explores the highly debated area of derivatives in Islamic finance and proposes a new way of creating a risk management tool that involves some elements of risk sharing.